Development of digital signal processing algorithms for power system protection - Xia, Yi Bin (2009)
Faults on the power systems may cause serious damage to the system apparatus, or even pose hazards to people. Therefore they should be detected and cleared as soon as possible. Among them the high impedance fault (HIF) is one of the most difficult protection problems, and still remains a long-standing challenge for power industry.